Properties of lithium under hydrothermal conditions revealed by in situ Raman spectroscopic characterization of Li2O-SO3-H2O (D2O) systems at temperatures up to 420 °C - Wang, X.; Wang, X.; Chou, I.; Hu, W.; Wan, Y.; Li, Zhen (Elsevier Science BV, 2017)
© 2017 Elsevier B.V.Lithium (Li) is an important component of hydrothermal fluids, especially submarine hydrothermal fluids. Investigation of the species and ion complexation of Li+ at elevated temperature and pressure can improve our knowledge on the behavior of Li under hydrothermal conditions. In this study, in situ optical and Raman spectroscopic experiments were conducted on the Li2SO4-H2SO4-H2O system and its D2O analogue at temperatures = 420 °C. An unexpected liquid-liquid phase separation (immiscibility) was observed at temperatures above 336.5 °C; the aqueous phase was separated into a sulfate-rich heavy liquid phase and a sulfate-poor light liquid phase at vapor-saturation pressures. The liquid-liquid phase separation temperature decreased as the Li2SO4 concentration increased in dilute solutions (= 1.25 m), increased as the Li2SO4 concentration increased in concentrated solutions (> 1.25 m), and exhibited a lower critical solution temperature (LCST) at ~ 336.5 °C. The presence of excess H2SO4 (or D2SO4) increased the liquid-liquid phase separation temperature at a constant Li2SO4 concentration. Liquid-liquid phase separation is common in organic-bearing solutions, and LCST is considered to be a macro-scale property of polymer solutions, indicating complicated ion pairing between Li+ and SO42 - at high temperature. In situ Raman spectra of the v1(SO42 -) band indicated the presence of “free” SO42 -, LiSO4-, possible Li2SO40 and other poly-ion associations. The Li+-SO42 - association increased with increasing temperature at a constant Li2SO4 concentration. These results indicate that Li+ can form contact ion pairs with ligands despite its strong hydration tendency. In submarine hydrothermal systems, various contact ion pairs should be important Li species during the high-temperature leaching of Li from basalts (e.g., > 200 °C). The formation of strong and various Li+-SO42 - pairs can enhance the leaching of Li because the mobility and diffusion of the Li+-SO42 - complex has been reported to be stronger than that of “free” ions. During the low-temperature (e.g., < 150 °C) uptake of Li+ into secondary minerals (e.g., clays), free Li+ and outer-sphere ion pairs are the dominant Li+ species. Contact ion pairs are also important Li species during the hydrothermal alteration/precipitation of Li-rich minerals in pegmatite systems. Moreover, liquid-liquid phase separation was found to play important roles in the formation of low-temperature minerals (e.g., calcite). However, similar crystallization pathways have rarely been documented for inorganic systems under high temperatures. Anhydrous Li2SO4 was observed to precipitate within the dense liquid phase at = 360 °C in 1.5 m Li2SO4, confirming that the immiscible dense liquid phase can serve as a precursor for the crystallization of sulfates and other minerals under hydrothermal conditions. The possible processes for the dense-liquid-based crystallization by particle attachment can be summarized as (1) strong and reversible ion association induces liquid-liquid phase separation, (2) nucleation and crystallization within the dense liquid phase, and (3) continued growth on the surface of early formed solid phase. Submarine hydrothermal fluids often contain low-dielectric components such as methane and other organic components, which lower the dielectric constant of hydrothermal fluids and promote ion association. Therefore, liquid-liquid phase separation may occur in submarine hydrothermal fluids and can play important roles in the precipitation of sulfates and other minerals.